Debt and Poverty; Is There Unsolicited Intimacy Between These Two Variables and the Disadvantaged Black South African Communities? An Examination of the Life of Informal Settlers in Gauteng South Africa - Nyoka, Charles (Acta Universitatis Danubius. Œconomica, 2025)
This study explored the conditions of individuals living in informal settlements in South Africa, focusing on their employment status, poverty, and debt levels. The research sort to understand the interrelationships between informal employment, borrowing practices, and poverty among residents of informal settlements and in addition sort to establish whether there is involuntary association between poverty, and debt within the community that live in the informal settlements. A chi-square test was used to examine potential associations between these variables. These findings suggest that as poverty levels increase, debt levels also tend to increase, highlighting the financial challenges faced by individuals in informal settlements. To the best of the researcher’s knowledge, extraordinarily little if any has been said about this community with respect to poverty and debt from a literature perspective. From that perspective, this paper pioneers’ debate on the plight of residents from informal settlements with respect to its association with poverty and debt and builds on the little that is there in literature about this community on this important subject.